The Thermodynamic Study of Turbocharger Pressure Ratio and Ambient Temperature Variation on Exergy Destruction Estimation of Homogeneous Charge Compression Ignition Engine Cogeneration System - Trivedi, Shailesh Kumar; Haleem, Abid (Asian Review of Mechanical Engineering, 2012)
Homogeneous Charge Compression Ignition (HCCI) technology is different from conventional combustion technologies. It has the combination of lean and premixed fuel air mixture and charge is compression ignited so it has multiple ignition points throughout the combustion chamber thus eliminating the high peak temperature inside the combustion chamber. This new engine technology is helpful in production of ultra low NO and particulate emissions. The use of lean and X unthrottled operation yields higher efficiency and better fuel economy also. In this paper, a new HCCI engine combined cycle cogeneration system is proposed and studied. The system is equipped with turbocharger, fuel vaporizer, engine, catalytic converter, different components of Organic Rankine cycle (ORC) and further heat recovery steam generator (HRSG) for waste heat utilization from the exhaust gases to obtain process heat. An exergy analysis is applied to the different components of HCCI engine cogeneration system to examine the thermodynamic losses in terms of exergy destruction and the effect of ambient temperature and turbocharger pressure ratio is obtained. The result shows a ranking among the components of the system on the basis of thermodynamic losses or the exergy destruction. This paper shows how an exergy method can yield effect of ambient conditions and design parameters values to reduce losses in various components of HCCI engine cogeneration system.